Behavioral responses to fevers and other medical events in children with and without ASD. Issue 11 (26th September 2022) - Byrne, Katherine; Zheng, Shuting; Bishop, Somer; Boucher, Juliana; Ghods, Sheila; Kim, So Hyun; Lord, Catherine
Abstract: Anecdotal reports and a small number of research studies suggest possible behavioral improvements in children with autism spectrum disorders (ASD) during a fever. However, previous studies rely largely on retrospective reports of this phenomenon. Establishing a robust association between fever and reduction of ASD‐related symptoms would promote opportunities for the development of innovative therapeutic interventions for children with ASD. In the current study, prospective data were collected from 141 children with ASD and 103 typically developing (TD) controls using parent responses to an 11‐item behavioral survey. Behaviors when no illness was present, during a fever, the week after a fever, and during non‐febrile illnesses for TD and ASD children were compared. Profiles of cases in which caregivers reported consistent behavioral improvements during fever are described. Data indicated worsening social, emotional/behavioral, and somatic symptoms during a fever regardless of diagnosis, with children with ASD demonstrating greater worsening of behaviors during a fever than TD children. Only three out of 141 children with ASD demonstrated consistent behavioral improvements during a fever; these children had a range of cognitive and adaptive skills. Children with ASD had stronger negative responses to fever than TD children. These findings contradict previous literature suggesting behavioral improvements for children with ASD. While improvements may occur for some children, it does not appear to be a common phenomenon. Additional research is needed to elucidate the nature of behavioral improvements in the subset of children with ASD who may respond positively to fever. Lay Summary: This study examines behavioral changes during fever and other medical events in children with autism compared to behavioral changes in a typically developing control group. Previous research and consistent subjective reports from parents and pediatricians suggest the possibility of behavioral improvements for children with autism during a fever. There is a lack of methodically collected data examining these effects. In the current study, children with autism consistently had stronger and more frequent negative behavior changes during fever than typically developing children (who also primarily showed worsening of behavior during fevers). Three out of 141 autistic children, and no typical children, showed improvements in varied areas during fevers.